Customary and Islamic Practices in Inheritance Distribution: Insights from The Gampong Customary Court in Pidie - Ismail, Faisal Husen; Muzana, Zaitun; Hamat, Zahri; Sulong, Jasni (Fakultas Syariah UIN Sulthan Thaha Saifuddin Jambi, Indonesia, 2024)
This study explores the methods of inheritance distribution employed by the Gampong Customary Court (Peradilan Adat Gampong) in Pidie. The research aims to shed light on the foundations and decision-making processes behind resolving inheritance disputes in the court. Using a descriptive qualitative approach, the study incorporates both secondary and primary data. Secondary data were gathered through literature reviews of dissertations, books, journals, and newspaper articles, while primary data were collected through interviews. A purposive sampling method was employed, selecting eight informants, including community leaders, religious figures, customary leaders, and intellectuals. A pilot study was conducted to ensure the relevance and accuracy of interview questions. Content analysis was used to examine both primary and secondary data. The study found that the Gampong Customary Court primarily relies on Islamic law and local customs when handling inheritance disputes. This study highlights several practical implications for inheritance management in Pidie, Aceh. The application of ijbari principles ensures compliance with Islamic teachings while respecting local customs. Practitioners must be proficient in both legal frameworks. Additionally, the suloh/syura model, which prioritizes consensus and dialogue, can be employed to resolve inheritance disputes and foster family harmony. Therefore, this study recommends strengthening the role of local leaders in resolving inheritance conflicts to build community trust and reduce the caseload in Sharia courts.